PVSAT Optical strategy to boost glass sales in Sintang City - Larasati, Cindy; Sari, Rachi Titi Ramadhani; Astikawati, Yunita (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
Pvsat Optics is a private company operating in the eye health sector. Glasses are one of the products at Optik Pvsat. Glasses are a visual aid for someone who suffers from nearsightedness or farsightedness. This research aims to determine Pvsat Optical's strategy for increasing glass sales in Sintang. The research method used in this research is descriptive qualitative research. Data collection techniques in this research were collected by interviewing customers, documentation, and observation. This research shows that Optik Pvsat uses several strategies to increase sales, namely conducting training for employees and implementing marketing strategies by utilizing social media. Promotions implemented by Optik Pvsat include promotions online and in person. Online promotions include social media such as WhatsApp and Instagram, while offline promotions include banners/billboards or direct education to customers. This education conveys the customer's benefits of using glasses.